Death and Rebirth Motifs in Sylvia Plath's Poetry: A Critical Explanation - Suman, Shambhunath (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 3 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
This article provides a critical explanation of the pervasive death and rebirth motifs in the poetry of Sylvia Plath. It argues that these themes are not merely expressions of a morbid obsession but constitute a central, cyclical framework through which she explores complex issues of identity, trauma, and female agency. The abstract posits that Plath's poetic "deaths" are multifaceted, ranging from literal considerations of suicide to metaphorical ends of a past self, an oppressive identity, or a state of psychological suffocation. These acts of annihilation are invariably linked to a subsequent, often violent or defiant, "rebirth" that signifies a radical transformation. Through close readings of key poems like "Lady Lazarus," "Ariel," and "Daddy," the paper demonstrates how this cycle functions as a powerful artistic strategy for confronting personal and societal pressures. It reveals that the rebirth is not a gentle resurrection but a willed, aggressive act of self-creation, often symbolized by fire, light, or an ecstatic breaking away. The study concludes that this dualistic motif of death as a precondition for rebirth is the engine of Plath's most powerful work, transforming her personal suffering into a universal language of resilience and radical self-liberation.